The Relationship Between Dietary Compliance (Dietary Patterns, Physical Activity, and Diabetes Medication Use) and HbA1c Levels in Patients with Type 2 Diabetes Mellitus Aged 25–55 Years - Rizki Rahma Wati; Fatma Syukrina (International Research of Multidisciplinary Analysis, 2025)
Type 2 Diabetes Mellitus (T2DM) is a global health issue that requires effective glycemic control to prevent complications. This study aims to investigate the relationship between adherence to dietary patterns, physical activity, medication use, and HbA1c levels in T2DM patients aged 25–55 years. This study employs a case study approach with an observational design. Data were collected through interviews, questionnaires, medical records, and HbA1c laboratory tests. Key findings indicate that adherence to a healthy diet, regular physical activity, and taking antidiabetic medications as prescribed are significantly associated with lower HbA1c levels. Patients who are more compliant with these three aspects tend to have better glycemic control. The conclusion of this case study emphasizes the importance of a comprehensive approach involving lifestyle interventions and optimal medication management to achieve effective glycemic control in working-age T2DM patients. These findings support the need for ongoing education and adequate support for patients to improve their adherence to therapeutic recommendations